The Influence of Physical Activities and Sleep Quality on Cardiovascular Disorders in the Elderly - Ainul Ghurri; Laily Mita Andriana; Danuditya Purna Atmaja (Science Midwifery, 2022)
With age, many body functions decline, and the structure and function of cells, tissues, and organ systems change. Such changes can cause muscle weakness, affect the ability to participate in physical activity, and can affect sleep quality. The sampling technique used in this study was direct sampling. A sample of 56 elderly aged 50 years and over was obtained. Physical activity was measured using the Elderly Physical Activity Scale (PASE) questionnaire, and sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Based on the result analysis of the relationship test using the chi-square test, the p-value obtained from the results of the statistical significance test was 0.5 > 0.05. This shows no relationship between physical activity and sleeps quality in the elderly at Poshandu Mawar, Menur Pampangan, Sukolilo District, Surabaya City.